2019
DOI: 10.1002/jsfa.9982
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origin traceability of Keemun black tea based on its non‐volatile composition combined with chemometrics

Abstract: BACKGROUND Non‐volatile compounds play a key role in the quality and price of Keemun black tea (KBT). The non‐volatile compounds in KBT samples from different producing areas normally vary greatly. The development of rapid methods for tracing the geographical origin of KBT is useful. In this study, we develop models for the discrimination of KBT's geographical origin based on non‐volatile compounds. RESULTS Seventy‐two KBT samples were collected from five towns in Anhui province to determine 13 KBT compounds b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…As a first step in assessing how tea metabolites are related to diverse genetic backgrounds, we sought to expand our knowledge of tea metabolites by untargeted metabolomic analysis. Previous untargeted analyses were limited to processed tea products or fresh leaves of a small group of closely related tea cultivars 20 , 26 , 28 , 30 , 47 , 48 . We anticipate that many tea metabolites were missed in these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step in assessing how tea metabolites are related to diverse genetic backgrounds, we sought to expand our knowledge of tea metabolites by untargeted metabolomic analysis. Previous untargeted analyses were limited to processed tea products or fresh leaves of a small group of closely related tea cultivars 20 , 26 , 28 , 30 , 47 , 48 . We anticipate that many tea metabolites were missed in these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the differences of region conditions including temperature, precipitation and altitude (Fang et al., 2017; Liang et al., 2008), previous studies showed the differential compounds contributed to the identification of geographical origin (Fang, Huang et al., 2019; Fang, Ning et al., 2019; Xin et al., 2018). Based on the differential metabolites related to production place (Supporting information Table S1) and tea cultivar (Supporting information Table S2), KEGG metabolic pathway analysis was carried out with Arabidopsis thaliana as the corresponding species (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies based on tea constituents have attempted to distinguish between tea types (Jiang et al., 2019; Zhou et al., 2019), geographic origins (Fang et al., 2019) and cultivars (Zheng et al., 2018), it is still unclear which compounds can be used as markers for the classification of the main C. sinensis tea types. To figure out the most prominent indicators of all detected compounds and assess their potential for tea classification with different fermentation processes, the levels of free amino acids, catechin, alkaloid, and GA, as well as a combination of all these compounds in tea samples were determined using PCA (Figure 3).…”
Section: Resultsmentioning
confidence: 99%